Efektivitas penggunaan media pembelajaran digital dalam memotivasi belajar siswa pada materi Pendidikan Agama Islam - Aziz, Ismi; Taqwa, Hafiz (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This research aims to describe the effectiveness of using digital learning media, specifically the Quizizz platform, in motivating students to learn Islamic Religious Education (PAI) material at SMA Negeri 2 Bogor. The background of this study is the low motivation of students towards PAI subjects and the need for innovative learning media that is relevant to the characteristics of the digital generation. This study uses a qualitative approach with a descriptive method. Data collection techniques are conducted through observation, interviews, and documentation. The results of the research show that the use of Quizizz can increase enthusiasm, active participation, and students' learning spirit in PAI lessons. Quizizz provides an interactive and enjoyable learning experience through its competitive gamification features. Supporting factors for the implementation of this media include the availability of digital infrastructure, student enthusiasm, and teacher readiness. Meanwhile, the inhibiting factors include the limitations of devices and internet networks, as well as the lack of digital literacy among some teachers and students. In conclusion, the use of the digital learning media Quizizz is effective in increasing student motivation in Islamic Education subjects at SMA Negeri 2 Bogor. Abstrak Penelitian ini bertujuan untuk mendeskripsikan efektivitas penggunaan media pembelajaran digital, khususnya platform Quizizz, dalam memotivasi belajar siswa pada materi Pendidikan Agama Islam di SMA Negeri 2 Bogor. Latar belakang penelitian ini adalah rendahnya motivasi belajar siswa terhadap mata pelajaran PAI dan perlunya inovasi media pembelajaran yang relevan dengan karakteristik generasi digital. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penggunaan Quizizz mampu meningkatkan antusiasme, partisipasi aktif, dan semangat belajar siswa dalam pembelajaran PAI. Quizizz memberikan pengalaman belajar yang interaktif dan menyenangkan melalui fitur gamifikasi yang kompetitif. Faktor pendukung implementasi media ini antara lain adalah ketersediaan infrastruktur digital, antusiasme siswa, serta kesiapan guru. Adapun faktor penghambatnya meliputi keterbatasan perangkat dan jaringan internet, serta kurangnya literasi digital sebagian guru dan siswa. Kesimpulannya, penggunaan media pembelajaran digital Quizizz efektif dalam meningkatkan motivasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di SMA Negeri 2 Bogor.